#TITLE_ALTERNATIVE# - SEIZARWATI (NIM 22710303) pembimbing : Prof. Ir. Lambok M. Hutasoit, M.Sc., Ph.D. : Agus M. Ra, WULAN
Umbulan Spring is a big spring located in Kabupaten Pasuruan which is categorized as second type of spring (1 – 10 m3/ sec). The discharge rate of the spring in 2012 was 4002 liter/ sec, while it was 5262.4 liter/ sec in 1987 and 4591.2 liter/ sec in 1990. This thesis attempts to discuss the cause of the depletion of the Umbulan spring. There are two hypotheses that are commonly used to explain the depletion, i.e.: 1) groundwater abstraction by industry located in thedownstream of the spring, 2) decrease in recharge area caused by deforestation in the upstream of the spring. In order to test which hypotheses is valid to answer the depletion, geoelectric survey, analysis of stable isotopes, hydrogeochemistry, and satellite imagery have been carried out. The result of geoelectric survey shows that the Umbulan Spring is located in unconfined aquifer system. The result of isotope analysis shows that the Umbulan spring has been affected by evaporation, which also shows that the spring is located in unconfined aquifer system. Based on hydrogeochemistry analysis, the Umbulan spring contains bicarbonate as the dominant anion and the TDS value is relatively low. It shows a strong correlation with recharge area and the aquifer of Umbulan Spring is thought to be in the upper zone. Meanwhile, deep wells in the downstream of Umbulan Spring are located in deepaquifer system. It is characterized by self flowing artesian groundwater level and the isotopic composition is not affected by evaporation. It means that Umbulan Spring is located in different aquifer system from the industrial wells. Therefore, it is less likely that groundwater abstraction influences the depletion of Umbulan Spring. The analysis of satellite imagery shows that there has been deforestation in recharge zone about 58.7% in the period of 1994 – 2002. Since Umbulan Spring is located in unconfined aquifer system, the change in the recharge zone will affect the discharge rate in the short time. Therefore, the depletion of Umbulan Spring is most likely caused by land use change in the recharge zone of the spring.